Discussion of ?A new approach of selecting real input ground motions for seismic design The most unfavourable real seismic design ground motions? by C-H Zhai and L-L Xie. - Moustafa, Abbas (Earthquake engineering & structural dynamics.)
This discussion consists of two parts. The first part raises a few comments and questions on the method presented in the above paper. The second part proposes a measure for identifying resonant accelerograms in a set of earthquake records without the need for pre-processing of the records or inclusion of the structure dynamic analysis.